Release of tissue inhibitor of metalloproteinase-2 from alginate microcapsule encapsulating genetically engineered cells - Kim YS (Dove Medical Press, 2013)
Yeon Seong Kim,1,* Young-Il Jeong,2,* Shu-Guang Jin,2 Jian Pei,2 Min Wen,2 In-Young Kim,1 Kyung-Sub Moon,1 Tae-Young Jung,1 Hyang-Hwa Ryu2, Shin Jung1–3 1Department of Neurosurgery, 2Brain Tumor Research Laboratory, 3Chonnam National University Research Institute of Medical Sciences, Chonnam National University Hwasun Hospital and Medical School, Jeollanam-do, Korea *These authors contributed equally to this work Background: In this study, 293T cells were genetically engineered to secrete tissue inhibitor of metalloproteinase-2 (TIMP2) and encapsulated into alginate microcapsules to continuously release TIMP2 protein. Methods: The anti-invasive potential of the microcapsules was studied in vitro using brain tumor cells. The TIMP2 gene was transfected to 293T cells, and genetically engineered 293TIMP2 cells were encapsulated into alginate microcapsules. Release of TIMP2 protein was detected with Western blot analysis and the anti-invasive potential against U87MG cells was tested using gelatin zymography and a Matrigel assay. Results: Cell viability within the alginate microcapsules was maintained at a cell density of 5 × 106. Because polycationic polymers are helpful for maintaining the mechanical strength of microcapsules with good cell viability, the alginate microcapsules were reinforced with chitosan (0.1% w/v). Expression of TIMP2 protein in cell lysates and secretion of TIMP2 into the conditioned medium was confirmed by Western blot analysis. Alginate microcapsules encapsulating 293TIMP2 cells released TIMP2 protein into the medium efficiently, where the TIMP2 protein participated in degradation of the matrix metalloproteinase-2 enzyme and inhibited invasion of U87MG cells. Conclusion: Alginate microcapsules encapsulating 293TIMP2 cells are promising candidates for anti-invasive treatment of glioma. Keywords: 293T cells, tissue inhibitor of metalloproteinase-2, alginate microcapsule, therapeutic protein